Intravenous methadone for perioperative acute and chronic pain management in Chinese adult cardiac surgical patients: A protocol for pilot randomized controlled trial - Henry Man Kin Wong; Wai Tat Wong; Xiaodong Liu; Sylvia Siu Wah Au; Randolph Hung Leung Wong (PLoS ONE, 2025)
Background Postoperative pain is significant in cardiac surgical patients. Perioperative analgesia with intermittent administration of opioids can result in significant fluctuations in serum opioid concentrations. Methadone should provide a rapid onset and long-term pain relief upon a single intravenous dose at induction of anesthesia, and may reduce chronic postsurgical pain (CPSP) in cardiac surgical patients. The feasibility of using intravenous methadone in Chinese cardiac surgical patients, and its effect on acute and chronic pain management after cardiac surgery will be evaluated. Methods A single-center, prospective, randomized-controlled pilot trial. Adult cardiac surgical patients will be randomized to receive 0.2 mg/kg methadone or morphine at induction of anesthesia. Patient-controlled analgesia morphine protocol, oral paracetamol and dihydrocodeine will be given for postoperative analgesia. Venous blood sampling for plasma methadone concentration will be obtained at regular intervals from study drug infusion to 96 hours after administration. The primary outcome will be a description of study feasibility, encompassing recruitment and retention, protocol adherence and stakeholder acceptability. Secondary outcomes include the time of ventilator weaning to spontaneous breathing, time of extubation, morphine requirements within 24 hours and 72 hours after surgery, time to first morphine rescue, postoperative pain scores, patient satisfaction, and length of stay in ICU and hospital. Opioid-related side effects including sedation, nausea and vomiting, and time to first bowel opening will be recorded. CPSP will be assessed with Neuropathic Pain Scale and Pain Catastrophizing Scale at 3 and 6 months after surgery. Discussion Randomized controlled trials on intravenous methadone in cardiac surgical patients are scarce, with none in Chinese populations. This study, supported by plasma methadone concentration analysis, will establish a basis for future large-scale research aimed at improving recovery through optimized pain management. Clinical trial registration ClinicalTrials.gov NCT05913284.